Hoist & haul 2010 proceedings of the International Conference on Hoisting and Haulage - Brokenshire, Peter; Andersen, Susan (Society for Mining Metallurgy, 2010)
Hoist and Haul 2010 is a compilation of the papers delivered at the prestigious "2010 International Conference on Hoisting and Haulage." It provides the most current, cutting-edge insights into important issues faced by today's mining professionals, including the ever increasing challenges of larger, more efficient, and safer ore handling systems, new developments in technology, and the design decisions greatly influenced by these advancements.